Evaluation of N Îµ-(carboxymethyl)lysine and lipid peroxidation in multiethnic Malaysian subjects with type 2 diabetes mellitus - Ahmed, K.A.A.; Muniandy, S.; Ismail, I.S.; Ali, R.S.; Alhamodi, Z.H. (2011)
The glycoxidation product, N Îµ-(carboxymethyl)lysine (CML), is formed during reaction of glucose with protein under oxidative conditions. The aim of the study was to evaluate the levels of the most common glycoxidation product; N Îµ-(carboxymethyl)lysine (CML) and the most advanced lipoxidation product, malondialdehyde (MDA) in type 2 diabetic Malay, Indian, and Chinese ethnic groups in the Malaysian population. Studies were performed on age-matched Malay, Indian, and Chinese subjects with type 2 diabetes mellitus. Different biochemical parameters including serum levels of CML, MDA, lipid profile, glucose, and hemoglobin A1c (HbA 1c) were measured by standard methods. The relationships between circulating CML and lipids, HbA1c, and MDA, were examined. Correlation studies between CML, lipids, HbA 1c, and lipid peroxidation were performed. CML and MDA levels were significantly higher in Malay subjects than in Indian or Chinese patients (p <0.005). A significant difference was also observed in the levels of serum total cholesterol and LDL-cholesterol (p <0.05) between the groups in the study. A positive correlation was observed between serum levels of CML and MDA in Malay diabetic patients, but no such correlation was seen in either the Chinese or Indian populations. The results of this study demonstrate that ethnicity affects CML and MDA circulating levels in Malaysian subjects with type 2 diabetes mellitus. Â© 2011 Academic Journals.